Management of bacterial wilt (Ralstonia solanacearum) of potato: focus on natural bioactive compounds (Journal of Biodiversity Conservation and Bioresource Management, 2018)
The bacterial wilt disease caused by Ralstonia solanacearum is an extremely destructive soil borne bacterial pathogen to potato. It appeared as rapid and fatal wilting symptoms in the host. The pathogen entered through different wounds and easily disseminated via infected biological material, soil, contaminated irrigation water, surface water, farm equipment etc. and could survive for many years in association with alternate hosts. It is a widely distributed and very much diversified soil borne pathogen having an unusually broad host range with long-term survivable ability. Direct yield losses caused by the pathogen varied from 30 to 90% depending on different factors such as cultivar, weather factors, soil type, cropping pattern and strain etc. Bacterial wilt continued to be an economically serious problem for field-grown potatoes in many tropical, subtropical and warmer areas of the world including Bangladesh. But the effectiveness of conventional management is limited because of some special biological features of the bacteria. Mostly protective methods and chemical control remain ineffective, antibiotics show hardly any effect, and efficacious biocontrol method has yet to be developed against the organism. However, during the recent decades, some natural bioactive compounds, viz. propolis, honey, turmeric, magnesium chloride, cow dung, aromatic rice extract, iodine, sodium bicarbonate etc. have got attention for their effectiveness in inhibiting a range of serious bacterial pathogens from both Gram positive and Gram negative types. As no conventional method has been found effective alone, such compounds could be tested for their effectiveness against the very successful soil borne bacteria to overcome the traditional management limitations.J. Biodivers. Conserv. Bioresour. Manag. 2018, 4(1): 73-92